Karakterisasi Tebal Lapisan Dan Ketahanan Korosi Mild Steel SS400 JIS G3101 Dengan Metode Elektroplating Ni-Cr - Pakanna, Adi Aprians; Sumual, Hendro Maxwell; Pomalingo, Moh Fikri; Mansjur, Zuldesmi (Jurnal Mesin Nusantara, 2024)
Mild steel is steel with a concentration of carbon element below 0.3%. In its use as an oil storage tank material on fuel transport trucks, there is a problem, namely its resistance to corrosion in fuel. Sulfur compounds in fuel have a role in the formation of corrosion. Currently, the Ni-Cr electroplating coating method is very widely used as an effort to control the corrosion rate of carbon steel. The use of Ni-Cr as an anode is relied upon as a substance resistant to corrosion. Therefore, the purpose of this study was to identify how layer thickness affects corrosion levels in SS400 mild steel based on current variations and duration of the electroplating process. In this study using mild steel SS400 JIS G3101 with electroplating method (electroplating) varying the electric current 1A, 2A and 3A, as well as electroplating time of 10 minutes, 20 minutes and 30 minutes. The test parameters of the electroplating results are the actual layer thickness test, theoretical thickness test and corrosion rate test. Data processing was analyzed using two-way variance analysis. The thickness of the layer increases with increasing electric current and the length of time of Ni-Cr electroplating. The highest thickness value of 102.34 μm using a digital microscope while for theoretical testing of 98.33 μm, both were obtained at a current variation of 3A and an electroplating time of 30 minutes. The trend of corrosion rate value will decrease with the increase in electric current and the length of electroplating time with the lowest value of 0.003359 mmpy at a variation of electric current 3A and electroplating time of 30 minutes. For optimal values with the lowest corrosion rate on mild steel SS400 JIS G3101 as an oil storage tank material on fuel transport trucks, it is obtained by using a current of 3A and an electroplating time of 30 minutes Ni-Cr.